1996
DOI: 10.1177/088307389601100404
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Outcomes After Pediatric Closed Head Injury: Relationships With Age, Severity, and Lesion Size

Abstract: This study investigated the behavioral outcomes and adaptive functioning of 138 children with mild to severe closed head injury in the 6- to 16-year age range. Each child was evaluated with the Personality Inventory for Children-Revised. A subset of this sample (n = 77) received the Vineland Adaptive Behavior Scales. Results revealed little evidence for group differences based on severity of closed head injury on scales associated with psychopathology on the Personality Inventory for Children-Revised. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 14 publications
3
41
0
Order By: Relevance
“…Consequently, we used a high score (IIS3) as a threshold in order to consider only the most severe impairments, for which the uncertainty of the prediction is low. The description of injuries associated with such impairments, as well as the similarity in our results compared to those of previous studies with respect to the functional outcome following a TBI, indicate that our predictions are realistic [13,14,37,38].…”
Section: Discussionsupporting
confidence: 77%
“…Consequently, we used a high score (IIS3) as a threshold in order to consider only the most severe impairments, for which the uncertainty of the prediction is low. The description of injuries associated with such impairments, as well as the similarity in our results compared to those of previous studies with respect to the functional outcome following a TBI, indicate that our predictions are realistic [13,14,37,38].…”
Section: Discussionsupporting
confidence: 77%
“…Recent research indicates that trauma (eg, anoxia) is more likely to impair developing skills and the development of new skills, while leaving previously developed skills relatively intact. 16,17 This hypothesis suggests that language skills that are developing during the toddler years might be more impaired when a child experiences an anoxic insult during the first year of life (ie, before development of the skill) and that language skills might be less affected by an anoxic insult after they have already been acquired (ie, after 42 months).…”
Section: Discussionmentioning
confidence: 97%
“…For example, recent data indicate that a majority of children with severe TBI receive postinjury special education services. 16 Although previous studies have documented the effects of TBI on children's adaptive behavior skills, 4,7,10,17,18 other aspects of children's functional status have received little attention. Several studies have demonstrated that functional disability is common within the year after a pediatric injury.…”
mentioning
confidence: 99%